Enhancing Investment Intention through Return and Risk: The Role of Financial Technology Among Millennial Generation - Ahmad Syaukani (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Purpose: This study aims to investigate the influence of perceived risk and perceived return on investment interest among Indonesian millennials, and to examine whether fintech moderates the relationship between perceived risk and investment interest. The research focuses on millennial employees of PT Brantas Abipraya as the target population. Methods: An explanatory quantitative design was applied using path analysis with SEM PLS. The study involved 170 millennial respondents selected from PT Brantas Abipraya. The research instrument measured investment interest, fintech, perceived risk, and perceived return, adapted from validated constructs in previous studies. Key features of the analysis included model measurement, structural assessment, and evaluation of the moderating effect of fintech. Results: The findings indicate that perceived risk negatively affects investment interest, while perceived return shows a significant positive effect. The moderating influence of fintech on the relationship between perceived risk and investment interest was found to be insignificant. The results highlight that perceptions of risk and return remain the primary drivers of investment decisions, regardless of fintech adoption. Implications: The study suggests the need to strengthen financial literacy and reduce perceived risk, particularly through fintech platforms, to enhance capital market participation among the younger generation. Further research should examine external determinants of investment behavior and incorporate longitudinal approaches to capture changes over time in investment interest